Massive hemorrhage protocol activation in obstetrics: a 5-year quality performance review. (May 2019) - Margarido, C.; Ferns, J.; Chin, V.; Ribeiro, T.; Nascimento, B.; Barrett, J.; Herer, E.; Halpern, S.; Andrews, L.; Ballatyne, G.; Chapmam, M.; Gomes, J.; et al.
Highlights: Seventeen massive haemorrhage protocol events among 19 790 deliveries (0.09%). Areas of improvement were consistent laboratory testing and hypothermia monitoring. Over-transfusion occurred more often than under-transfusion. The majority of hemorrhages were due to uterine atony and abnormal placentation. In many cases there was no documentation of a debrief after protocol termination. Abstract: Background: A structured approach to hemorrhagic emergencies in obstetrics has gained popularity with the implementation of massive hemorrhage protocols. The trauma literature suggests that routine quality reviews should be in place to improve patient outcomes. The aim of this study was to develop quality indicators and assess compliance by the clinical team. Methods: A multidisciplinary team set the institutional quality indicators for the massive hemorrhage protocol review. A retrospective review of all obstetrical massive hemorrhage protocol activation events from September 2010 to January 2015 was performed. All protocol events occurred before the creation of the quality indicators. Data were retrieved from patient records. Results: There were 17 (0.09%) protocol activations for 19 790 deliveries during the study period. All 17 (100%) patients received at least one unit of red blood cells. Overactivation, defined as the transfusion of <2 units of red blood cells, occurred in two cases (12%). Common causes of non-compliance were: 24% (4/17) temperature monitoring, 18% (3/17) lactate measurement, 41% (7/17) arterial blood gas sampling, and 18% (3/17) hemoglobin maintenance within the target range of 55–95 g/L. Admission to intensive care and peripartum hysterectomy occurred in 12 and 5 cases (71% and 29%), respectively. Conclusions: Suboptimal compliance was found in multiple areas, which may be attributable to the low frequency of activation of our massive haemorrhage protocol in obstetrics. The quality targets identified in this report can act as a basis for other institutions developing quality indicators to evaluate performance.